2009
DOI: 10.2353/ajpath.2009.080752
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Induced Gene-3 Is Expressed in Human Atheroma Plaques

Abstract: Atherosclerosis is characterized by a complex immune response in the vessel wall, involving both inflammation and autoimmune processes. EpsteinBarr virus-induced gene 3 (Ebi3) is a member of the interleukin (IL)-12 heterodimeric cytokine family, which has important immunomodulatory functions. To date, little is known about the role of Ebi3 in vascular disease. We examined the expression of Ebi3 in human atheromatous lesions and analyzed its transcriptional regulation in vascular cells. The in situ expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 52 publications
6
56
0
4
Order By: Relevance
“…However, according to recent reports, EBI3 is also expressed in other cell types, including intestinal epithelium and aortic smooth muscle cells (36,37). Our results suggested that epidermal keratinocytes as well as Treg express EBI3, and this expression was decreased in the SSc skin.…”
Section: Discussionsupporting
confidence: 43%
“…However, according to recent reports, EBI3 is also expressed in other cell types, including intestinal epithelium and aortic smooth muscle cells (36,37). Our results suggested that epidermal keratinocytes as well as Treg express EBI3, and this expression was decreased in the SSc skin.…”
Section: Discussionsupporting
confidence: 43%
“…*, p Յ 0.05; **, p Յ 0.005; ***, p Յ 0.0005; NS, not significant. addition, strong co-expression of Ebi3 and p35 in smooth muscle cells, endothelial cells, and macrophages of advanced lesions in patients with symptomatic carotid plaques (40) and positive correlation of plasma IL-35 levels with the left ventricular ejection fraction in a large number of CAD patients (41) has led to the hypothesis that IL-35 may be involved in amelioration of atherosclerosis and improved prognosis in CAD (42). Here we provide strong evidence that IL-35 can play a key role in the amelioration of plaque burden in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…IL-27 is expressed in atherosclerotic plaques 93 , and its role in atherosclerosis has been reported in cultured cells, animal models and coronary patients with inconsistent findings. In IL-27-deficient (Ldlr 94 .…”
Section: Il-27mentioning
confidence: 99%
“…On the other hand, the expression of IL-35 increased significantly in ApoE −/− mice with attenuated plaque. In fact, coexpression of the two subunits of IL-35 has been demonstrated in human advanced atherosclerotic plaque 93 . Decreased levels of IL-35 have been reported in patients with acute coronary syndrome (unstable angina pectoris and acute myocardial infarction) compared to a chest pain syndrome group; IL-35 levels also positively correlated with left ventricular ejection fraction whose reduction is associated with heart failure 109 .…”
Section: Il-35mentioning
confidence: 99%